Immunogenicity of Streptococcus pneumoniae 74 kDa Surface Protein in Rabbit Model (Bangladesh Journal of Microbiology, 2016)
Immunogenicity of a pneumococcal 74 kDa surface protein in the rabbit model was investigated in this study. For this, Streptococcus pneumoniae serotype 7F was collected and water extraction procedure was applied for the preparation of surface materials, which was used for further isolation of the 74 kDa surface protein. Rabbits were immunized with the sonicated nitrocellulose membrane containing the 74 kDa surface protein and the control group of rabbits was injected with same concentration of sonicated nitrocellulose membrane only. The antibody response against the 74 kDa surface protein was evaluated by both ELISA and immunoblot assay. Sera collected from the 74 kDa surface protein immunized rabbits were examined and the high titre (1:1600) ELISA values (OD490) indicated the production of adequate amounts of anti-74 kDa antibodies in the rabbits. In the immunoblot analysis, a single antigenic band was obtained on the nitrocellulose membrane treated with sera obtained from rabbits immunized with the 74 kDa surface protein. The high titre antibody production in the rabbits indicates the immunogenicity of the 74 kDa surface protein in rabbit model.Bangladesh J Microbiol, Volume 31, Number 1-2,June-Dec 2014, pp 25-28